Trends for Development of Bulgarian Agricultural Cooperatives - Miteva, Albena (Research Papers, 2006)
The purpose of the paper is to analyze and assess the specific mechanism of functioning of the contemporary cooperative structures in agriculture and on this basis to offer potential solutions and suggestions for their future development in the EU pre-accession period. On this basis are depicted variants for enhancing the organizational cooperative statute, concrete solutions for transforming and reconstructing the agricultural productive cooperatives in service agricultural cooperatives which with common money funds and equipment will provide mechanical, trade and credit services to family agricultural farms of the cooperative members, and are suggested trends for the development of credit cooperatives.